LANDSCAPE ART IN "BOBURNOMA" - Rozmatova Mukhlisa daughter of Yoldoshkhoja (American Journals, 2023)
This article is about Landscape art used in Babur's work "Boburnoma". Opinions and comments about Babur's art depiction skills are presented.
Keywords: Babur,